KAJIAN STILISTIKA DALAM NOVEL PULANG KARYA TERE LIYE: DIKSI, MAJAS, DAN CITRAAN - Maula, Nikmatul; Ahada Wahyusari; Asri Lolita; Musliha; Fabio Testy Ariance Loren; Maulida Mustado (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the stylistic elements in Tere Liye's novel Pulang, focusing on diction, figures of speech, and imagery. This research employed a qualitative descriptive approach. The data source was the novel Pulang by Tere Liye, while the data consisted of words, phrases, clauses, and sentences containing stylistic elements. Data were collected through reading and note-taking techniques, then analyzed by classifying the data into diction, figures of speech, and imagery, followed by interpretation based on stylistic theory. Data validity was ensured through persistent observation. The findings indicate that Tere Liye employs various forms of diction, figures of speech, and imagery to strengthen aesthetic value, deepen characterization, and convey messages effectively. Diction is used to create emotional nuances and emphasize meaning, figures of speech enrich the expressive quality of language, while imagery evokes sensory experiences that enable readers to visualize the events vividly. These findings demonstrate that stylistic elements contribute significantly to enhancing the literary quality and communicative power of the novel.